Effect of defects and film thickness on the optical properties of ZnO–Au hybrid films. Issue 51 (5th June 2015) - Saravanan, K.; Krishnan, R.; Hsieh, S. H.; Wang, H. T.; Wang, Y. F.; Pong, W. F.; Asokan, K.; Avasthi, D. K.; Kanjilal, D.
<x xml:space="preserve">Abstract</x> Thickness and defects effects on the optical properties of ZnO–Au hybrid films were studied using optical and electronic structural studies.